PSYCHOLOGICAL PREPARATION OF COACHES TO WORK WITH ATHLETES WITH AUTISM SPECTRUM DISORDERS - Vorobyov, S.A.; Gretsov, A.G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to scientific substantiation of the technology of psychological preparation of trainers for interaction with persons with autism spectrum disorders. Methods and structure of the study. Analysis of literary and other information sources, summarizing the experience of specialists, survey, focus group. The collection of empirical data was carried out during the implementation of advanced training courses “Psychological training of coaches for work in sports for people with intellectual disabilities” (teacher A.G. Gretsov), 18 specialists participated. Results and conclusions. A program of psychological training of coaches to work with athletes with autism spectrum disorders is proposed, designed to increase the effectiveness of interaction with them, as well as personal satisfaction with professional activities. It is advisable to include in the psychological training of trainers working in this field: the study of the psychological characteristics of people with autism spectrum disorders; training in the development of special communication skills for working with this contingent; mastering the basic techniques of psychological support for such athletes; personal training (realization of the subjective meaning of work in this area, search for personal resources, etc.).